ANALISIS CEMARAN AIR LIMBAH PADA SUMUR BOR DI SEKITAR RPH RUMINANSIA CIPTAKARYA PANAM PEKANBARU - Elvi Syahrina; Mirna Ilza; Amilia Linggawati (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2021)
The objectives of this reserch are to analysis the wastewater content of Ruminasiat RPH Pekanbaru City and compare it with the quality standard of waste water, namely PermenLH No.5/2014. Then analysis the quality of bore well water used by the community around the RPH Ruminansia and compare it with Permenkes No.416 / Men.kes / Per / IX / 20 and analysis the social economic impact of the community living around the RPH. The wastewater parameters measured were BOD, COD, TSS, fatty oil, organic nitrogen and pH. While the parameters of the wellbore water are color, odor, taste, TDS, pH, nitrate, nitrite, sulfate, and total coliform.The results of reseach show indicate that Ruminansia RPH wastewater is above the quality standard, except for the pH parameter. Meanwhile, drilled well water with a distance of approximately 5 meters does not meet the quality standards for clean water quality including total coliform and nitrate parameters, well water with a distance of 50 meters meets the requirements for clean water quality that can be utilized by the surrounding community.